The Role of Memory in LLMs: Persistent Context for Smarter Conversations (International Journal of Scientific Research and Management (IJSRM), 2024)
Memory in LLMs has given way to more logical and sensible interactions between the system and the user. This is different from other models that are session bound, such that the responses to any one query are not related to past and future interactions with the same user, but memory-enabled LLMs retain information across sessions and continually update interactions with the person they are communicating with. The role of permanent memory in LLMs is considered in this work, provided through the analysis of the role of memory mechanisms in maintaining conversation flows, improving user interaction, and supporting practical applications in various industries, including customer service, healthcare, and education. Discussing how the idea and architectures of memory correspond to storage and retrieval procedures and the management of memory in LLMs this paper outlines the opportunities and challenges for AI systems that want to include contextual intelligence but also remain ethical. The synthesis of important concepts underlines the promising prospects of memory-augmented models in improving the communication with users and points to the imperatively important aspect of controlling the memory process at the design stage of LLMs. We also offer recommendations for privacy and ethical concerns that should be avoided in the case of future AI memory advancements in an effort to pursue sustainable technological progress while also incorporating user-oriented values into the process.